Pendekatan Probabilistik dalam Evaluasi Investasi dan Manajemen Portofolio - Khoerunnisa, Hana; Wulan, Elis Ratna (Jurnal Ekonomi Dan Statistik Indonesia, 2024)
The probabilistic approach in investment evaluation and portfo-lio management has become a crucial tool for measuring and man-aging risk. This article explores various probabilistic concepts and techniques used in finance, including Value at Risk (VaR), Condition-al Value at Risk (CVaR), and stress testing. Additionally, basic proba-bility theory, probability distributions, and random variables are discussed to provide a comprehensive understanding of the appli-cation of probability in investments. The analysis includes the use of probabilistic models to evaluate expected value and investment risk, including through Monte Carlo simulations and the Capital Asset Pricing Model (CAPM).In portfolio management, modern portfolio theory and the effi-cient frontier are explained to optimize portfolios to maximize ex-pected returns and minimize risk. The concept of diversification and its benefits in reducing portfolio risk are also outlined. While the probabilistic approach offers many advantages, this article also ex-amines the limitations of probabilistic models, including reliance on historical data and assumptions of normal distribution. Steps to address these limitations, such as model calibration and backtesting, are also discussed.